Insights from the amphioxus genome on the origin of vertebrate neural crest - Yu, Jr-Kai (Cold Spring Harbor Laboratory Press, 2008)
The emergence of the neural crest has been proposed to play a key role in early vertebrate evolution by remodeling the chordate head into a “new head” that enabled early vertebrates to shift from filter feeding to active predation. Here we show that the genome of the basal chordate, amphioxus, contains homologs of most vertebrate genes implicated in a putative neural crest gene regulatory network (NC-GRN) for neural crest development. Our survey of gene expression shows that early inducing signals, neural plate border patterning genes, and melanocyte differentiation genes appear conserved. Furthermore, exogenous BMP affects expression of amphioxus neural plate border genes as in vertebrates, suggesting that conserved signals specify the neural plate border throughout chordates. In contrast to this core conservation, many neural crest specifier genes are not expressed at the amphioxus neural plate/tube border, raising the intriguing possibility that this level of the network was co-opted during vertebrate evolution. Consistent with this, the regulatory region of AmphiFoxD, homologous to the vertebrate neural crest specifier FoxD3, drives tissue-specific reporter expression in chick mesoderm, but not neural crest. Thus, evolution of a new regulatory element may have allowed co-option of this gene to the NC-GRN.